Sailing directions for the islands of Newfoundland and coast of Labrador [electronic resource] : including the straits of Belle Isle and banks of Newfoundland : with particular directions for the several bays, harbours, roadsteads, islands, rocks, shoals, sands &c. - Blachford, William. (London : R. & W. Blachford)
Electronic reproduction. Mode of access: Internet. 44